Persepsi Dukungan Organisasi dan Kesejahteraan Psikologis pada Perawat yang Menangani Pasien Covid-19 di Kota Bekasi: Annisa Sulistiawanti, Rika Fitriyana - Sulistiawanti, Annisa; Fitriyana, Rika (Fakultas Psikologi Universitas Bhayangkara Jakarta Raya, 2022)
The COVID-19 pandemic that hit Indonesia caused a large number of positive COVID-19 patients to be treated. Care for patients who are positive for COVID-19 is the responsibility of health workers, one of which is a nurse. The surge in the number of patients who must be given treatment is a stressor for nurses which can result in low psychological well-being. The stress experienced by nurses comes from the workplace, which is the hospital. The hospital must create a work environment that contributes to the welfare of its nurses to create a good perception of organizational support for nurses.The purpose of this study is to see a relationship between perceptions of organizational support and psychological well-being in nurses treating COVID-19 patients. The subjects in this study were nurses treating COVID-19 patients and worked in hospitals located in Bekasi city using purposive sampling technique. The sample amounted to 123 nurses which was calculated using the Slovin formula with an error rate of 10% based on a population of 2,718 nurses. The measuring instrument in this study is the perceived organizational support scale and the psychological well-being scale using the Likert scale. This study uses the Pearson Product Moment correlation test with a result of 0.610 and a significance value of 0.00 (p <0.05). the result in this study indicate that there is a relationship between perceived organizational support and the psychological well-being of nurses who treat COVID-19 patients.